Physiological and Molecular Responses to Main Environmental Stressors of Microalgae and Bacteria in Polar Marine Environments - Lauritano, Chiara (Microorganisms, 2020)
The Arctic and Antarctic regions constitute 14% of the total biosphere. Although they differ in their physiographic characteristics, both are strongly affected by snow and ice cover changes, extreme photoperiods and low temperatures, and are still largely unexplored compared to more accessible sites. This review focuses on microalgae and bacteria from polar marine environments and, in particular, on their physiological and molecular responses to harsh environmental conditions. The data reported in this manuscript show that exposure to cold, increase in CO(2) concentration and salinity, high/low light, and/or combination of stressors induce variations in species abundance and distribution for both polar bacteria and microalgae, as well as changes in growth rate and increase in cryoprotective compounds. The use of -omics techniques also allowed to identify specific gene losses and gains which could have contributed to polar environmental adaptation, and metabolic shifts, especially related to lipid metabolism and defence systems, such as the up-regulation of ice binding proteins, chaperones and antioxidant enzymes. However, this review also provides evidence that -omics resources for polar species are still few and several sequences still have unknown functions, highlighting the need to further explore polar environments, the biology and ecology of the inhabiting bacteria and microalgae, and their interactions.